Dynamic optimization of CRT pacing using a novel algorithm improves survival in a real-world cohort of patients. (14th October 2021) - Gold, M.R; Zimmerman, P; Singh, J.P
Abstract: Background: The AdaptivCRT (aCRT) algorithm continuously adjusts cardiac resynchronization therapy (CRT) according to intrinsic atrioventricular (AV) conduction status, providing synchronized left-ventricular pacing in patients (pts) with a normal PR interval and adaptive biventricular (BiV) pacing in pts with a prolonged PR interval. Prior secondary analyses of prospective trials demonstrated a reduction in mortality and atrial fibrillation incidence with aCRT. Objective: To compare mortality in a large real-world population of pts with and without aCRT using electronic health record (EHR) data. Methods: An Optum® de-identified EHR dataset and Medtronic CareLink device data were linked to identify pts (age>18 years) with a CRT implanted between 2014–2018 who survived ≥35 days post implant and with a documented baseline left ventricular ejection fraction (LVEF). Pts were grouped with aCRT set to either Adaptive BiV+LV (aCRT group) or standard CRT (control group). Two pt subgroups were identified: (i) pts with left bundle branch block (LBBB) and no AV block, (ii) pts with either no LBBB or with AV block. Kaplan-Meier curves and log-rank were used to estimate and compare survival between treatment and control groups in both the full cohort and subgroups. Multivariate Cox regression was used to estimate the aCRT treatment effect while controlling for baseline characteristics. Results: Among 8624 patients implanted with a CRT device with EHR data available for a median of 23.5 months post implant [IQR: 12.6, 37.3], 3994 patients had the aCRT feature activated. Pts in the aCRT group were younger (median 69 [IQR:60, 76] vs 73 [IQR: 65, 79] years), more frequently female (35% vs 26%), and more frequently had LBBB (72% vs 51%); p's<0.001. Median QRS duration was 150ms (IQR: 133, 164) for the aCRT group and 152ms (IQR: 134, 172) for the control group (p<0.001). Median LVEF was 22% (IQR: 18, 30) for the aCRT group and 25% (IQR: 20, 30) for the control group (p<0.001). Through 60 months post implant, the overall mortality rate was 23.6% (95% CI: 20.7%-26.3%) for the aCRT group and 37.6% for the control group (95% CI: 34.9%-40.1%), p<0.001. Subgroup analysis demonstrated a significant reduction in mortality with aCRT in both pts with LBBB without AV block (Figure, left panel) and pts without LBBB and with AV block (Figure, right panel). After accounting for baseline differences, the reduction in mortality remained significant in the LBBB/no AV block group (HR: 0.54, 95% CI: 0.39–0.76, p<0.001) and trended toward significance in the no LBBB/with AV block group (HR: 0.89, 95% CI: 0.79–1.01; p=0.08). Conclusion: In a large, real-world population of pts implanted with CRT devices, the AdaptivCRT algorithm was associated with significantly reduced mortality, with a greater reduction observed among pts with LBBB and without AV block. These results are being tested prospectively in the ongoing AdaptResponse multi-national, randomized clinical trial. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Medtronic, Inc.